(3eMGSHI GdeDSSGJ GdafObjI (B:s (3efgL Ydej dJNWjW h QbGHI h bjGS GdBOGA GdafObj (B/s - (3YdGe, eMeO fHjds ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1992)
(3GSGSjGJ GdfXGe GdeMGSHj aj GdafGOb(B, (3GdGfTWI h GdhXGFa GdafObjI GdafjI h GdeYGhfI GVGaI Gdi GdOaGJQ h GdbjhO h GdOhQGJ GdeSJfOjI GdafObjI(B, (3GdLQO h GdMSGHGJ GdNJGejI GdafObjI h cPG GdehGRfGJ GdJNWjWjI GdafObjI(B, (3GdGSGdjH GdJMdjdjI aj GdafGOb(B.s
(3edGMb U(B.409 , (3eQGLY U(B.429s
Keywords: (3GdafGOb (B- (3eMGSHIs; (3GdeDSSGJ GdafObjIs; (3eMGSHI GdafGObs